Determining Pedestrian Level of Service for Selected Footpath Stripes of Dhaka City Using Multi-criteria Decision Making Approach (Journal of Bangladesh Institute of Planners, 2018)
Walking is considered to be the most important mode of travel across the world, particularly for short distance trip. Since 19.6% of the trips are made by foot in Dhaka, it is necessary to ensure friendly walking environment in the footpath for the welfare of pedestrians of Dhaka. This study aims to make a comparative analysis of Pedestrian Level of Service (PLOS) of selected footpath stripes along Segun Bagicha road, Toynbee Circular road, Mirpur road and Baily road. Pedestrian Level of Service has been determined based on ten factors: path width, pedestrian volume, crossing facilities, availability of buffer, distance from vehicular traffic, surface quality, comfort, walking environment, existence of street light. Weight of each factor has been determined through Multi-criteria analysis approach, Analytical Hierarchy Process (AHP). Path width, Pedestrian volume and existence of buffer have been found to be first, second and third most important factors. PLOS has been determined based on indexed value of factors and weight of factors. All the sections were found to have poor PLOS. The findings of the study will be helpful for the transport policy makers to ameliorate the condition of these factors to ensure a better walking condition for pedestrians of selected footpath sections.JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 67-76